The Effect of Antimicrobial Addition to Protein Whey Based Edible Film on the Gouda Cheese Physical Quality During Ripening - Andriani, Ria Dewi; Sawitri, Manik Eirry; Al Awwaly, Khothibul Umam; Manab, Abdul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
The objective of this study was to identify the effect of the addition of antimicrobial agent (benzoic and propionic acid) to protein whey based edible film on the Gouda cheese physical quality during ripening. The functional properties of Gouda cheese was analyzed, including colour, texture and microstructure. The results revealed that the addition of benzoic and propionic acid gave significant effect statistically (p<0.05) on yellowness (b*), but insignificant effect (p>0.05) on texture, brightness (L*) and redness (a*) of Gouda cheese. The results also showed that ripening time significantly affected (p<0.05) on texture and brightness (L*) of Gouda cheese, but did not affect on redness (a*) and yellowness (b*). Microstructure of Gouda cheese with the addition of benzoic acid indicated that the dispersion of fat globules was more uniform, meanwhile the dispersion of matrix protein was more uniform with the addition of propionic acid. Generally, microstructure of Gouda cheese showed that the dispersion of fat globules and matrix protein was more uniform in four months ripening time.Keywords: Edible Film, Protein Whey, Gouda Cheese, Antimicrobial agent